Basic mechanical engineering a textbook for first year students of engineering - Chavan, D.K; Pathak, G.K (Standard Book House, 2009)
It gives us great pleasure, to present a text book on 'Basic Mechanical Engineering'. This introductory text is intended to first year students of Engineering and has been strictly written according to the new-revised syllabus of various universities.